ELIMINATION OF CHRONIC PELVIC PAIN CAUSED BY ADENOMYOSIS THE PROGESTOGENS NEW GENERATION - M. R. Orazov; A. V. Chayka; E. N. Nosenko (Акушерство, гинекология и репродукция, 2016)
Endometriosis, with more than centenary history, remains a challenge in our day. One of the more common options is adenomyosis, the share of which amounts to 80%. The aim of the study was to evaluate the clinical effectiveness and tolerance to resolve with chronic pelvic pain syndrome of adenomyosis the use of progestogen-new generation dienogest in a dose of 2 mg for 6 months. The study included 44 (n=44) women of reproductive age with a diagnosis of adenomyosis with chronic pelvic pain syndrome of various degrees of severity, whose average age was on average 36 yo 2 years who received therapy with dienogest in a daily dose of 2 mg for 6 months. The results showed high therapeuticefficiency dienogest in the treatment of pelvic pain caused by adenomyosis.